Influence of the control law on oscillatory processes in electromechanical drive - Alexander V. Klimov (Вестник СибАДИ, 2025)
Relevance. Currently, vehicles with electromechanical power transmission and electrochemical battery as the energy source are being registered on the road network. These are electric vehicles used as personal transport, electric buses as public passenger transport, electric cargo vehicles used for various needs. The main feature of this transport is related to providing the required power reserve for 1 charge. To do this, it is necessary to use advanced power transmission components, energy sources and control methods to minimize energy consumption. Since the processes in the electromechanical power transmission run at high speeds, in the motor control circuit with frequencies up to 10 kHz or more, situations of exciting oscillatory phenomena occur where low inertia and rigidity of the external mechanical characteristics of the electric motor are observed. In particular, the modes of changing driving conditions (traction, driven, braking) are of importance, which are accompanied by a change in the direction of force in the contact zone of the wheel and the road and the direction of load application in the gears. This process is accompanied by reconnection, i.e. meshing of the other side of the teeth. With a rapid change in torque, this process can be accompanied by a shock followed by excitation of frictional vibrations. Therefore, it is important to effectively control the torque to eliminate these negative consequences.The purpose of the study. It is necessary to check the influence of the S-shaped law of torque setting in the control of an electromechanical power transmission on the dynamic load of a mechanical transmission and on the energy efficiency of movement.Materials and methods. The study of the influence of the law of torque setting was carried out based on experimental research methods.The results of the study. The S-shaped law of torque setting has shown the possibility of eliminating vibrations excitation when changing the driving mode and the direction of load application in the mechanical transmission of the power transmission. A high value of the regenerative torque when releasing the pedal and moving in braking mode results in reduced movement efficiency, increased specific energy consumption per 1 kilometer.Conclusion. The application of the S-shaped law of torque setting is suitable for the implementation of motion control algorithms and software.